Exploration of physical features of homogeneous–heterogeneous chemical action in a nanofluid film dispensed with MOS2 in diathermic oils - P. Bala Anki Reddy (Taylor & Francis Group, 2021)
Topical endeavour is made to describe and search out the flow characteristics correspond to nano flow over thin liquid film dispensed with Molybdenum disulphide (MOS2) in a Casson fluid past an unsteady exponentially stretching sheet in porous medium. Due to this problem is modelled to boost the rate of thermal transfer of Diathermic oils, particularly, Kerosene-oil (KO) and Engine-oil (EO) by considering uneven heat source/sink. The governing equations are standardized into a system of ordinary differential equations by means of similarity transformations. The elucidation of the physical problem is conquered by shooting technique. The impact of pertinent parameters on flow and heat transfer is deliberated with the aid of graphs and tables. It is shown that the rate of heat transfer enhances by adding MOS2 in engine oil than MOS2 in kerosene oil, which improves its lubrication properties. The current conclusions are promoted academic research, tribology and polymer industry.